#1**+1 **

Rather conveniently, from the first equation, we have $4x = 4y \rightarrow x = y$.

Thus, we can plug this into the second equation to get $y = 2y+6$. Solving this equation gives us $\boxed{y = -6}$, which is our solution.

xCorrosive Jun 3, 2021

#1**+1 **

Best Answer

Rather conveniently, from the first equation, we have $4x = 4y \rightarrow x = y$.

Thus, we can plug this into the second equation to get $y = 2y+6$. Solving this equation gives us $\boxed{y = -6}$, which is our solution.

xCorrosive Jun 3, 2021